Acupuncture for a First Episode of Acute Ischaemic Stroke: An Observer-Blinded Randomised Controlled Pilot Study. Issue 5 (October 2016) - Liu, Ching-Hsiung; Hsieh, Yu-Ting; Tseng, Hung-Pin; Lin, Hung-Chih; Lin, Chun-Liang; Wu, Tai-Yi; Lin, Shu-Hua; Tsao, Szu-Hung; Zhang, Hong
Objective: To determine the required sample size for, and feasibility of, a RCT examining the effectiveness of early acupuncture for acute ischaemic stroke. Methods: Thirty-eight patients aged 40–85 years with a first episode of acute ischaemic stroke presenting within 72 h of stroke onset were randomly assigned to receive manual acupuncture (MA group; n=20) plus standard care or standard care only (control group, n=18). The acupuncture treatment was provided daily for 2 weeks. The primary outcome was the change in the National Institutes of Health Stroke Scale (NIHSS) score between baseline and 4 weeks. Secondary outcomes included changes in the Fugl–Meyer assessment (FMA) and the functional independence measure scores between baseline and 4 weeks, and changes in NIHSS, Barthel Index and modified Rankin Scale scores at 12 weeks. Results: Thirty-one patients completed the study (dropout rate=18%) and adverse effects were minimal. No significant differences were seen between groups in the improvements in NIHSS scores, although there tended to be a greater reduction in NIHSS score after 1 week in the MA group relative to the control group (p=0.066). The post-stroke motor activity at 4 weeks was associated with a significantly increased FMA score in the acupuncture group compared with the control group (p<0.05), but not supported by intergroup analysis. Conclusions: This pilot study indicates that acupuncture appears to be safe for patients in the acute stage of ischaemic stroke. A subsequent trial with a larger sample size (estimated at n=122) is required to confirm whether early acupuncture intervention contributes to earlier functional improvement and to assess the longer-term clinical efficacy of acupuncture. Trial Registration Number: NCT02210988; Results.